96=-16x-6y

Simple and best practice solution for 96=-16x-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 96=-16x-6y equation:


Simplifying
96 = -16x + -6y

Solving
96 = -16x + -6y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '16x' to each side of the equation.
96 + 16x = -16x + 16x + -6y

Combine like terms: -16x + 16x = 0
96 + 16x = 0 + -6y
96 + 16x = -6y

Add '-96' to each side of the equation.
96 + -96 + 16x = -96 + -6y

Combine like terms: 96 + -96 = 0
0 + 16x = -96 + -6y
16x = -96 + -6y

Divide each side by '16'.
x = -6 + -0.375y

Simplifying
x = -6 + -0.375y

See similar equations:

| (x+1)13+5=8 | | x=-28+12x-x^220s | | (244)1/3 | | ax+c=-bx | | 3cos^2x+2sinx-3=0 | | -200x=150-5y | | 3*x^2-91*x+316=0 | | Y/7=18 | | 4x-5=6x+-7 | | y=cos(2pix) | | 2/128=x/22 | | 4(2x-7)-2(4x-14)= | | -7(x+9)=9(-4)-15x | | -10x+3y=-90 | | 3y+10x=-300 | | 2(19-3y)+6y=38 | | x=-28+12x-x^2 | | 5+2(3c-1)=c+21-4c | | 9x-37=3x-1 | | -300+2y=75x | | 3cosx=1-x | | g(x)=x^3f(x) | | 7a+3b+4a-9b= | | 4y=-25x-100 | | ln(x)+x-3=0 | | x^2-5*x-36=0 | | 15x^2+x-14=-8 | | 45x^3=5x | | ln(3x-19)=5 | | 4y-220=-100x | | x+17y=20 | | 18x^3-9x^2-5x-2=0 |

Equations solver categories